ON THE BIOLOGY OF PSETTODES ERUMEI (BLOCH & SCHN.), AN INDIAN HALIBUT - Das, M; Mishra, B (Indian Journal of Fisheries, 2011)
Studies on the biology of flatfishes have made remarkable progress due to the contribution of Dawes (1930), Jones (1952), Bagcnal (1957,1958,1962), Pitt (1964), Ryland (1966), Nordeng and Bratland (1971), Last (1978), Anon. (1980) and Liewes (1984).